Therapeutic potential of ADSCs in diabetic wounds: a proteomics-based approach - Gu, Yuan; Mu, Zelan; Chen, Yuanzheng; Wu, Can; Shi, Jie; Bai, Nan (Frontiers in Cell and Developmental Biology, 2024)
Background Diabetes mellitus (DM), a chronic metabolic disease characterized by elevated blood sugar, leads to delayed or non-healing wounds, increasing amputation risks, and placing a significant burden on patients and society. While extensive research has been conducted on adipose-derived stem cells (ADSCs) for promoting wound healing, there is a scarcity of studies focusing on diabetic wounds, particularly those employing proteomics and bioinformatics approaches. Objective This study aimed to investigate the mechanisms by which ADSCs promote diabetic wound healing using proteomics and bioinformatics techniques. Methods Healthy rat fat tissue was used to isolate ADSCs. A T2DM rat model with back wounds was established. The experimental group received ADSC injections around the wound, while the control group received PBS injections. Wound healing rates were documented and photographed on days 0, 3, 7, 10, and 14. On day 7, wound tissues were excised for HE and Masson’s staining. Additionally, on day 7, tissues were analyzed for protein quantification using 4D-DIA, with subsequent GO and KEGG analyses for differentially expressed proteins (DEPs) and protein-protein interaction (PPI) network analysis using STRING database (String v11.5). Finally, Western blot experiments were performed on day 7 wounds to verify target proteins. Results and Conclusions In all measured days postoperatively, the wound healing rate was significantly higher in the ADSC group than in the PBS group (day 7: p < 0.001, day 10: p = 0.001, day 14: p < 0.01), except on day 3 (p > 0.05). Proteomic analysis identified 474 differentially expressed proteins, with 224 key proteins after PPI analysis (78 upregulated and 146 downregulated in the ADSC group). The main cellular locations of these proteins were “cellular anatomical entity” and “protein-containing complex”, while the biological processes were “cellular processes” and “biological regulation”. The primary molecular functions were “binding” and “catalytic activity”, with GO enrichment focused on “Wnt-protein binding”, “neural development”, and “collagen-containing extracellular matrix”. Further analysis of PPI network nodes using LASSO regression identified Thy1 and Wls proteins, significantly upregulated in the ADSC group, as potentially crucial targets for ADSC application in diabetic wound treatment.